Prevalence of depression among geriatric population - Sindhu Gopal; Meena Chacko; Punita A Sharma; D Mitra (Indian Journal of Psychiatric Nursing)
Background: Life expectancy has increased in India, elderly population is currently the second largest in the world and 20% of illness in the elderly is due to mental or a neurological illness and the most common being dementia and depression. Aim of the study was to assess the prevalence of depression among geriatric population attending OPD of selected tertiary hospitals. Methods: A cross sectional descriptive study was conducted on 120 geriatric population attending Out Patient Departments of selected tertiary care hospital selected by stratified simple random sampling method. Tools: The questionnaire included section I, socio demographic data and section II Geriatric Depression Scale Short Form(GDS-SF). Ethical clearance obtained from institutional research ethical committee. Permission was obtained from tertiary hospital and informed consent was taken. Results: Prevalence of depression was 24.2%. Conclusion: with the gradual greying of population expected in India over the coming time, maintaining a good quality of life for the senior citizens is the need of the hour.